Respuesta :

Answer:

Step-by-step explanation:

To solve this inequality, we have to find x (or make x the subject of the inequality:

since     ⁻ˣ/₃  ≤ 6       [multiply both sides by 3]

               - x ≤ 18      [multiply both sides by -1; this flips the inequality sign]

              x ≥ - 18    [this is the solution]

To graph the inequality, draw the line x = - 18 with a solid line, and then shade the region that is x > -18.

We use a solid line because the point x = -18 is included. However, hypothetically,  if the inequality was x > -18 only, a broken line would be used to show that the line x = -18 is not included.

Ver imagen JoshEast
ACCESS MORE